2002
DOI: 10.1080/026886902753512655
|View full text |Cite
|
Sign up to set email alerts
|

Osteoid osteomas of the body of the cervical spine. Case report and review of the literature

Abstract: A case report of an adult patient with an osteoid osteoma of the body of the 3rd cervical vertebra is presented. The long history of progressively worsening nocturnal cervical pain which was relieved by non-steroidal anti-inflammatory drugs, and an essentially normal clinical examination, are typical of this condition; in which CT is the investigation of choice. Complete relief was obtained following excision of the lesion. The literature is reviewed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2007
2007
2010
2010

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 12 publications
0
8
0
Order By: Relevance
“…Suttner et al [8] surveyed the literature and identifi ed only fi ve previously reported cases of osteoid osteoma confi ned to the cervical spinal vertebral body. There have been two additional reports [1,5] on this problem, which make a total of seven cases presented in the literature.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Suttner et al [8] surveyed the literature and identifi ed only fi ve previously reported cases of osteoid osteoma confi ned to the cervical spinal vertebral body. There have been two additional reports [1,5] on this problem, which make a total of seven cases presented in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…Although MRI is not specifi c for osteoid osteomas, it is the best imaging technique for revealing the relationship between the tumour and the spinal cord. Plain radiographs of the cervical spine are usually negative because of the size of the lesion and the overlap of anatomical features [8] . Radionuclide bone scanning is positive in the majority of cases [8] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An osteoid osteoma in the spine shows a 70% to 100% propensity for posterior element involvement [6,8,16]. Excluding the posterior elements, cervical spinal osteoid osteomas have been reported in the dens axis [22], the lateral mass of C1 [4] or C5 [7], the vertebral body of C2 [4,20] or C3 [28], the transverse process of C2 [2] or C4 [21], and the pedicle of C3 [29], C5 [25,29], or C6 [18]. To our knowledge, however, there has not been any report of an osteoid osteoma in the pedicle of C2.…”
Section: Introductionmentioning
confidence: 99%
“…The spine is only affected in about 10% of the cases, with more than 50% involving the lumbar spine, here again, mainly (90%) the dorsal parts up to the origin of the pedicle; the body of the vertebra is involved in exceptional cases [7,14,16,17,20]. With regard to the cervical spine, an osteoid osteoma of the third cervical vertebra [21], the arc of the axis [8], the second vertebral body [18], the tranverse process of the axis [2] and the transverse process of the fourth cervical vertebra [19] have been reported in literature.…”
Section: Introductionmentioning
confidence: 99%